Personal Hygiene pada saat Menstruasi - Nanda Wahyudi; Dewi Riastawaty; Listautin (Jurusan Manajemen dan Bisnis Fakultas Ekonomi dan Bisnis Universitas Cenderawasih, 2023)
Personal hygiene during menstruation needs to be done properly to prevent the risk of infection in the reproductive organs, especially for teenage girls. From the results of the study, 69.6% of women had positive behavior in caring for genitalia and 31.01% had negative behavior. From this percentage, women who did not practice good menstrual personal hygiene tended to get infections. This community service activity aims to increase the knowledge of young female students at the Ma'Had Al-Mubarak Al-Islami Litahfizil Qur'an Al-Karim Islamic Boarding School regarding personal hygiene during menstruation. The methods used are lectures, demonstrations, pretest-posttest as well as discussions and questions and answers using educational videos with laptops, leaflets and LCD media. This community service activity received a positive response from the students, as evidenced by the enthusiasm of the students in asking questions. Based on the evaluation process, it was found that there was an increase in students' knowledge about personal hygiene during menstruation, this was proven by the post-counseling evaluation where 90% of participants were able to answer each post-test question given correctly. It is hoped that with this activity the students can be prepared to face the sexual, physical and psychological changes that occur to them and to maintain the health of their reproductive organs properly, one of which is by carrying out personal hygiene during menstruation.